2000
DOI: 10.1046/j.1439-0426.2000.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical studies of the gonadotropic cells in the pituitary gland of male mullet, Mugil cephalus, during the annual reproductive cycle in both natural habitat and captivity

Abstract: Summary Using antiserum specific for the β subunit of coho salmon gonadotropic hormone II (GTH II), an immunocytochemical study of Mugil cephalus (L.) pituitaries was conducted during the annual reproductive cycle of the male in both natural habitat and captivity. The gonadotropic potency of the pituitary gland in general underwent an obvious increase during testicular development, reaching a peak at the time of reproductive maturity. During the testicular cycle of M. cephalus, the GTH cells showed an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Somatolactin function in teleost fish is not yet fully established, since mode of action depends on the species considered (Kaneko, ). Some studies suggested that SL is involved in sexual maturity and smoltification in salmonid species (Rand‐Weaver et al, ; Bhandari et al, ; Onuma et al, ); and in adaptation to background and photoperiod changes (Zhu and Thomas, ; Ayson and Takemura, ); metabolism and acid‐base balance (Kakizawa et al, ; Zhu and Thomas, ), stress response (Rand‐Weaver et al, ), and reproductive physiology in non‐salmonid species (Mousa and Mousa, ; Honji et al, ). Furthermore, environmental variations, such as photoperiod and temperature changes, can influence the SL profile (Vargas‐Chacoff et al, ; Fiszbein et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Somatolactin function in teleost fish is not yet fully established, since mode of action depends on the species considered (Kaneko, ). Some studies suggested that SL is involved in sexual maturity and smoltification in salmonid species (Rand‐Weaver et al, ; Bhandari et al, ; Onuma et al, ); and in adaptation to background and photoperiod changes (Zhu and Thomas, ; Ayson and Takemura, ); metabolism and acid‐base balance (Kakizawa et al, ; Zhu and Thomas, ), stress response (Rand‐Weaver et al, ), and reproductive physiology in non‐salmonid species (Mousa and Mousa, ; Honji et al, ). Furthermore, environmental variations, such as photoperiod and temperature changes, can influence the SL profile (Vargas‐Chacoff et al, ; Fiszbein et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Mousa and Mousa () observed morphometrical variations in SL cells of Oreochromis niloticus and Mugil cephalus during the reproductive period, with higher synthetic and secretory activity during sexual maturation and spawning, suggesting that SL is involved in some reproductive processes. Furthermore, the larger nuclear area and higher OD observed in vitellogenic S. hilarii females (Honji et al, ) also suggests higher cellular activity during the reproductive period in this species.…”
Section: Discussionmentioning
confidence: 99%
“…Its production is still remaining restricted until the induced spawning techniques are developed. This allows these valuable aquaculture species to become available worldwide.Like females of many commercially important fishes, mullets fail to complete ovarian development and do not undergo final oocyte maturation (FOM), ovulation or spawning when reared in captivity (Mousa, 1994;Mousa and Mousa, 1997;El-Gamal, 1999 andMousa, 2010). To facilitate a steady supply of seeds, oocyte maturation and ovulation need to be induced.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to females of many commercially important fishes, mullet do not undergo final oocyte maturation (FOM), ovulation or spawning in captivity [1][2][3] . Consistently, the ova will not advance to final maturation and ovulation without exogenous hormone stimulation, but will undergo atresia and degenerate.…”
Section: Introductionmentioning
confidence: 99%